The DUSP26 phosphatase activator adenylate kinase 2 regulates FADD phosphorylation and cell growth - Kim, Hyunjoo; Lee, Ho-June; Oh, Yumin; Choi, Seon-Guk; Hong, Se-Hoon; Kim, Hyo-Jin; Lee, Song-Yi; Choi, Ji-Woo; Hwang, Deog Su; Kim, Key-Sun; Kim, Hyo-Joon; Zhang, Jianke; et al. (NATURE PUBLISHING GROUP, 2014)
Adenylate kinase 2 (AK2), which balances adenine nucleotide pool, is a multi-functional protein. Here we show that AK2 negatively regulates tumour cell growth. AK2 forms a complex with dual-specificity phosphatase 26 (DUSP26) phosphatase and stimulates DUSP26 activity independently of its AK activity. AK2/DUSP26 phosphatase protein complex dephosphorylates fas-associated protein with death domain (FADD) and regulates cell growth. AK2 deficiency enhances cell proliferation and induces tumour formation in a xenograft assay. This anti-growth function of AK2 is associated with its DUSP26-stimulating activity. Downregulation of AK2 is frequently found in tumour cells and human cancer tissues showing high levels of phospho-FADD(Ser194). Moreover, reconstitution of AK2 in AK2-deficient tumour cells retards both cell proliferation and tumourigenesis. Consistent with this, AK2(+/-) mouse embryo fibroblasts exhibit enhanced cell proliferation with a significant alteration in phospho-FADD(Ser191). These results suggest that AK2 is an associated activator of DUSP26 and suppresses cell proliferation by FADD dephosphorylation, postulating AK2 as a negative regulator of tumour growth.